2020
DOI: 10.3389/fpls.2020.00140
|View full text |Cite
|
Sign up to set email alerts
|

The Phytotoxicity of Meta-Tyrosine Is Associated With Altered Phenylalanine Metabolism and Misincorporation of This Non-Proteinogenic Phe-Analog to the Plant's Proteome

Abstract: Plants produce a myriad of specialized (secondary) metabolites that are highly diverse chemically, and exhibit distinct biological functions. Here, we focus on meta-tyrosine (m-tyrosine), a non-proteinogenic byproduct that is often formed by a direct oxidation of phenylalanine (Phe). Some plant species (e.g., Euphorbia myrsinites and Festuca rubra) produce and accumulate high levels of m-tyrosine in their root-tips via enzymatic pathways. Upon its release to soil, the Phe-analog, m-tyrosine, affects early post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 95 publications
(175 reference statements)
1
9
0
Order By: Relevance
“…Assumptions could therefore be made that the ST and CH accessions tested in our study also would have this allelopathic ability. Oxidation of phenylalanine results in the formation of L‐ m tyrosine, and incorporation of this nonproteinogenic amino acid in lieu of phenylalanine during protein synthesis can negatively affect protein folding and further metabolic function (Zer et al., 2020). In fact, this known allelochemical has been shown to reduce the growth of several plant seedlings including large crabgrass (Bertin et al., 2003; Bertin et al., 2007; Zer et al., 2020); hence, the decrease of smooth crabgrass biomass observed with these accessions could be attributed to L‐ m ‐tyrosine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assumptions could therefore be made that the ST and CH accessions tested in our study also would have this allelopathic ability. Oxidation of phenylalanine results in the formation of L‐ m tyrosine, and incorporation of this nonproteinogenic amino acid in lieu of phenylalanine during protein synthesis can negatively affect protein folding and further metabolic function (Zer et al., 2020). In fact, this known allelochemical has been shown to reduce the growth of several plant seedlings including large crabgrass (Bertin et al., 2003; Bertin et al., 2007; Zer et al., 2020); hence, the decrease of smooth crabgrass biomass observed with these accessions could be attributed to L‐ m ‐tyrosine.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation of phenylalanine results in the formation of L-m tyrosine, and incorporation of this nonproteinogenic amino acid in lieu of phenylalanine during protein synthesis can negatively affect protein folding and further metabolic function (Zer et al, 2020). In fact, this known allelochemical has been shown to reduce the growth of several plant seedlings including large crabgrass (Bertin et al, 2003;Bertin et al, 2007;Zer et al, 2020); hence, the decrease of smooth crabgrass biomass observed with these accessions could be attributed to L-mtyrosine. However, to what extent L-m-tyrosine aids in weed suppression in the field is unknown; for example, if all CH and ST cultivars in F. rubra L. aggregate exude this allelochemical, then why are all not weed suppressive?…”
Section: Crop Sciencementioning
confidence: 99%
“…91 Leaf necrosis has also been reported in m-tyrosine-treated Arabidopsis at a concentration of 40 μM. 92 Nonprotein amino acids are thought to have phytotoxic properties through their substitution of protein amino acids during translation, modifying protein folding as a result. 73 This mode of action has recently been verified for m-tyrosine, which is specifically misincorporated in place of phenylalanine.…”
Section: Benzoxazinoidsmentioning
confidence: 99%
“…73 This mode of action has recently been verified for m-tyrosine, which is specifically misincorporated in place of phenylalanine. 92 Despite its apparent specificity to plant proteins in terms of their mode of action, 73 there is evidence of allelopathy towards other organisms by m-tyrosine. A higher concentration than that required to confer phytoallelopathy (50 mM) results in antifeedant and toxic effects on the termite Coptotermes formosanus.…”
Section: Benzoxazinoidsmentioning
confidence: 99%
See 1 more Smart Citation